Land Subsidence Risk Asseessment in Karst Region, Case Study : Rongkop, Gunung Kidul, Yogyakarta-Indonesia - Putra, Doni Prakasa Eka (RWTH Aachen University, 2011)
Land subsidence occurences due to sinkholes are common to be found in Rongkop, Gunung Kidul, lndonesia. They 3re located in karst morphology. Land subsidence is a well-known pbcnomenon in this karst landscape- Recently, however, ithas occurred in the middle ofa setrlemc.l. rcsulting in a hoie of scveral melres in diamcle. and depth and oausing damage on several houses- According !o findings lrom field observation, the iand subsidence is due to the interactions of unfavourable moryhological conditions, weak engireering propefties of Iithology, struclural gcology and heavy raiDfall.. Many traces of si*ho1es and land subsidence can bc Iound close to the area of scltlemert, *hich may bear the dsk of considerable disasters to the habilants liying in thc region. The a\aareness of this potential risk has given .he reason to condxct land subsidence risk assessment, wirh the purpose to delineate the land subsiderce risk ir the Rongkop disrrict. In tlis study, the map oI land subsidence risk was deveiopcd bascd on five paramclers: slope degree, lithology, rehtive relief, dislrnce to lineaments of va11cy and land use. Applying rhe po itt coutrt sJstcm ntodel, weights for the firsl four paramctors were determined by using opinion based scores adopting a criterion of anatyiical Herarchy proccss (AHP) 10 reveal land subsidence susceplibilily- After thrt. a malrix cvaluation system wlt! applicd for ihe deierminarion of $e risk. The results reveal that the zones ofhigh.st risk are located in lbe settlement area along the valleys rhat show the coincidence wirh the siokholes locations.